Liberalising Deployment of Internet of Things Devices and Services in Large Scale Environments - Mihailovic, Andrej (Wireless personal communications, 2017)
There is an ongoing enormous expansion of Internet of Things devices and services in everyday life, notably in novel large scale urban environments called Smart Cities. There, availability and uses of Internet of Things by end users and businesses is mainly palpable subject to prior knowledge of the relevant providers and use of dedicated applications that are associated with them. This current reality can be largely ascribed to the property of “verticality” of autonomous Internet of Things eco-systems in Smart Cities, where Internet of Things devices (e.g. sensor nodes) are connected over a communication infrastructure to service-cloud platforms that deliver and process data that is then presented at the applications level. This paper explains possibilities for revolutionary changes needed towards liberalising deployment and visibility of IoT services and data associated with them. It advocates a conceptual approach termed “horizontal networking for Internet of Things” facilitating a more open and generic presence of Internet of Things through the proposed Internet of Things identification meta-data. The vision is built on needed novel practical features in the current communication setups. The features comprise combinations of the opportunistic and near-match search and discovery model, Internet of Things identification meta-data also reflecting the physical and network-based dimensions of devices’ locations, novel routing and data flow models emerging via Information-Centric Networking and changes required in the elements of the current telecommunication infrastructure and the Internet.